Pengaruh Kepuasan Kerja dan Komitmen Organisasional terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Mediasi (Suatu Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Hayati Rosna, Ros; Sia Niha, Simon; A. Manafe, Henny (Dinasti Review, 2023)
Previous research and relevant research are very useful for a research or literature review of a scientific work both examining the influence between variables and other factors that also influence a variable itself. This article discusses a literature review of factors that have an impact on employee performance, namely work motivation as an intervening variable, job satisfaction, and organizational commitment. This research is written by the author in order to build a hypothesis that also has an impact on each variable so that it can be used for further research. The results of this research include: 1) Job satisfaction has a positive and significant impact on work motivation; 2) Organizational commitment has a positive and significant impact on work motivation; 3) Job satisfaction has a positive and significant impact on employee performance; 4). Organizational commitment has a positive and significant impact on employee performance; 5); Work motivation has a positive and significant impact on employee performance; 6). Work motivation is able to mediate job satisfaction which affects employee performance; 7) Work motivation is able to mediate organizational commitment that affects employee performance. 8) Job satisfaction and organizational commitment simultaneously have a positive and significant impact on employee performance.